Społeczna odpowiedzialność biznesu i społeczna odpowiedzialność nauki – w poszukiwaniu analogii - Marcin Żemigała (Studia i Materiały)
The aim of the article is to identify the analogy between corporate social responsibility (CSR) and science social responsibility (SSR) on the basis of scientific research. Five research questions were formulated regarding trends in research in these two areas. Data for analyzes were obtained from the global bibliographic database Scopus and related to scientific articles from 1937 to 2019. The main analogies were identified. Scientific research in both areas began in the same period and is carried out mainly in social and management sciences. However, discrepancies have also been identified. Research on CSR has developed far more than SSR, which is still at an early stage of development. Research on CSR is conducted in leading countries in the scientific and academic arena, and SSR rather in countries entering it. CSR has knowledge sharing platforms in the form of reputable, profiled journals, while SSR research is published in journals of lower reputation and with general rather than strictly SSR profiles. Research in the field of CSR is detailed and more often cited, while those related to SSR are general and less frequently cited. After all, research from both areas seems to be promising and worth further development.